1989
DOI: 10.1111/j.1432-1033.1989.tb14710.x
|View full text |Cite
|
Sign up to set email alerts
|

Substrate‐modulated reactions of putidamonooxin

Abstract: 1. 4-Methoxybenzoate monooxygenase is fairly nonspecific. The enzyme system with putidamonooxin as its oxygen-activating component catalyses: (a) 0-, S-and N-demethylation; (b) the oxygenation of 4-methylbenzoate and 4-methylmercaptobenzoate, with formation of 4-carboxybenzyl alcohol and 4-carboxyphenylmethyl sulfoxide, respectively, and (c) attack of the aromatic ring of 4-and 3-hydroxybenzoate and 4-aminobenzoate, yielding 3,4-dihydroxybenzoate and 4-amino-3-hydroxybenzoate, respectively.2. Compounds which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
41
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 43 publications
4
41
0
Order By: Relevance
“…One early proposal whereby an Fe 3ϩ -(hydro)peroxo species attacks the substrate (illustrated in Scheme 3A) derived from studies on putidamonooxin. Using uncoupling substrates, which caused the production of hydrogen peroxide, in combination with solvent isotope effects, a ferric-peroxo intermediate was suggested as the species responsible for the demethylation and dihydroxylation reactions catalyzed by this enzyme (53)(54)(55)(56). More recently, this general mechanism has found support in the work of Lee (57), which showed that benzene acts as both a substrate and an uncoupler of NDO, generating H 2 O 2 during the reaction.…”
Section: Discussionmentioning
confidence: 69%
“…One early proposal whereby an Fe 3ϩ -(hydro)peroxo species attacks the substrate (illustrated in Scheme 3A) derived from studies on putidamonooxin. Using uncoupling substrates, which caused the production of hydrogen peroxide, in combination with solvent isotope effects, a ferric-peroxo intermediate was suggested as the species responsible for the demethylation and dihydroxylation reactions catalyzed by this enzyme (53)(54)(55)(56). More recently, this general mechanism has found support in the work of Lee (57), which showed that benzene acts as both a substrate and an uncoupler of NDO, generating H 2 O 2 during the reaction.…”
Section: Discussionmentioning
confidence: 69%
“…These data indicate that it was rather unlikely that some of the substrate analogs tested uncoupled electron transfer from substrate hydroxylation. Oxygen uptake due to substrate-dependent uncoupling of electron transfer rather than true oxygenase activity has been reported for a number of oxygenases, e.g., 4-methoxybenzoate monooxygenase (10,11,67), phthalate dioxygenase (7), and salicylate hydroxylase (71).…”
Section: Resultsmentioning
confidence: 99%
“…Lipscomb has proposed that the diiron-oxo clusters in methane monooxygenase are converted during catalysis to an [Fe(IV) ⅐ Fe(IV)]AO species, which would be a strong oxidant similar to the Fe(IV)AO species proposed for cytochrome P-450 (33). An iron-peroxo complex [FeO 2 ] ϩ has been proposed for the oxygenating species in 4-methoxybenzoate O-demethylase (56).…”
mentioning
confidence: 99%
“…In this context, it is of interest that NDO can catalyze O-dealkylation (41), N-dealkylation, and sulfoxidation reactions (32), which are also typical cytochrome P-450 reactions. Other non-heme iron oxygenases that catalyze reactions similar to those catalyzed by cytochrome P-450 are the soluble forms of methane monooxygenase (19,33) and 4-methoxybenzoate monooxygenase (56). Ammonia monooxygenase appears to be responsible for the cytochrome P-450-type reactions catalyzed by Nitrosomonas europaea (29,54).…”
mentioning
confidence: 99%